Association of chronic kidney disease with all-cause mortality in patients hospitalized for atrial fibrillation and impact of clinical and socioeconomic factors on this association - Bao, Min-qiang; Shu, Gui-jun; Chen, Chuan-jin; Chen, Yi-nong; Wang, Jie; Wang, Yu (Frontiers in Cardiovascular Medicine, 2022)
Background: Atrial fibrillation (AF) and chronic kidney disease (CKD) often co-occur, and many of the same clinical factors and indicators of socioeconomic status (SES) are associated with both diseases. The effect of the estimated glomerular filtration rate (eGFR) on all-cause mortality in AF patients and the impact of SES on this relationship are uncertain. Methods: This retrospective study examined 968 patients who were admitted for AF. Patients were divided into 4 groups based on eGFR at admission: eGFR-0 (normal eGFR) to eGFR-3 (severely decreased eGFR). The primary outcome was all-cause mortality. Cox regression analysis was used to identify the effect of eGFR on mortality, and subgroup analyses to determine the impact of confounding factors. Results: A total of 337/968 patients (34.8%) died during follow-up. The average age was 73.70±10.27 years and there were 522 males (53.9%). More than 39% of these patients had CKD (eGFR<60 mL/min/1.73 m2), 319 patients with moderately decreased eGFR and 67 with severely decreased eGFR. After multivariate adjustment and relative to the eGFR-0 group, the risk for all-cause death was greater in the eGFR-2 group (HR=2.416, 95%CI=1.366–4.272, p=0.002) and the eGFR-3 group (HR=4.752, 95%CI=2.443–9.242, p<0.00001), but not in the eGFR-1 group (p>0.05). Subgroup analysis showed that moderately to severely decreased eGFR only had a significant effect on all-cause death in patients with low SES. Conclusions: Moderately to severely decreased eGFR in AF patients was independently associated with increased risk of all-cause mortality, especially in those with lower SES.